2022
DOI: 10.3389/fitd.2021.824067
|View full text |Cite
|
Sign up to set email alerts
|

Case Series: Pediatric Human T-Lymphotropic Virus Type 1 and Its Clinical Expression

Abstract: PurposeHuman T-lymphotropic Virus type 1 (HTLV-1) was the first retrovirus to be identified and associated with oncogenic activity. It is estimated that approximately 10–20 million people in the world are infected with it. The clinical manifestations most commonly associated with HTLV-1 infection include T-cell leukemia/lymphoma and myelopathy associated to HTLV-1 infection. The purpose of this study is to describe clinical and demographic characteristics in pediatric patients with HTLV-1 infection.Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…In the case series published by Ingara et al in a pediatric population in southwestern Colombia with HTLV-1 positive, they found nutritional deficiencies, skin involvement, opportunistic diseases, autoimmune and/or chronic inflammatory diseases, polymyositis, and pulmonary involvement as clinical manifestations. The latter was found in half of the patients, but bronchiectasis was related to the co-diagnosis of opportunistic infections by M. tuberculosis and Aspergillus, which were not documented in our patient (35).…”
Section: Discussioncontrasting
confidence: 49%
“…In the case series published by Ingara et al in a pediatric population in southwestern Colombia with HTLV-1 positive, they found nutritional deficiencies, skin involvement, opportunistic diseases, autoimmune and/or chronic inflammatory diseases, polymyositis, and pulmonary involvement as clinical manifestations. The latter was found in half of the patients, but bronchiectasis was related to the co-diagnosis of opportunistic infections by M. tuberculosis and Aspergillus, which were not documented in our patient (35).…”
Section: Discussioncontrasting
confidence: 49%
“…9,15 Case 3 was partially described in a recent report on pediatric manifestations of HTLV-1 in Colombia. 16 However, ophthalmological manifestations were not described in detail then, and images of retinal lesions were not included in the original report. The patient was later classified as having Vogt-Koyanagi-Harada syndrome in relation to HTLV-1 infection.…”
Section: Therapeutic Advances In Infectious Diseasementioning
confidence: 99%